Early mulching increases yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
In alley-farming the greatest effect on crop yields comes when tree foliage is applied as a mulch just before the crop is planted. Therefore prunings cut later in the season can be fed to livestock without depriving the crop. Trials in Nigeria's...